Religião, migração e saúde mental: uma investigação a partir do trabalho realizado pelo “Instituto Sonhe” com famílias de imigrantes em São Paulo - Domingues, Nelson Luis Nunes (2023)
The increase in migratory flows in recent years has brought many challenges to societies around the world. In this context this master's thesis aims to study the intersections between Migration, Religion and Mental Health based on the experiences of Bolivian immigrants and their families assisted by Instituto Sonhe, in the city of Sao Paulo, Brazil. We relied on a qualitative methodology by combining individual interviews with the immigrants and staff members of Instituto Sonhe, a focus group meeting during which Bolivian immigrants shared experiences and challenges in the migratory process, and ethnographic observation of the religious gatherings at the Instituto, which follows a protestant (Baptist) denomination. . We discussed the theological assumptions underlying the work of the Instituto Sonhe and how they influence the lives and adaptation of Bolivian immigrants in the Brazilian context. We also addressed the impact of the interviewees' migratory trajectories on their quality of life and stress, as well as the role played by religiosity in coping with challenges resulting from the migration process. The hypothesis presented in this work is that Religion functions as a factor of cohesion, recognition and strengthening of psychosocial identity, having as a facilitator of this process the religious space offered in the context of the Instituto Sonhe, which works as a welcoming environment and a support and sociability network, thus generating a positive impact on mental health. We concluded with a discussion of the limitations of the study and possibilities for future investigations